LEGAL LIMITATIONS TO THE FREEDOM OF ECONOMIC ACTIVITY IN POLAND IN 1989–2003 - Janusz Paczocha; Wojciech Rogowski (Ekonomia i Prawo, 2006)
Economic freedom, which is the basis of the economic system and one of the most crucial development factors, is significantly restricted. Numerous regulations and restrictions in the economic activity occur virtually in all  countries. The research shows varied levels of regulations and their quality (Djankov, 2004). The undertaken study aimed to reveal and document variations and the extent of regulatory restrictions of economic activity in the Polish economy in 1989-2003. The study identifies all regulations restricting the pursuit of economic activity in the Polish law, including such forms as: concessions, business activity permits and licenses, admissions of products, goods or equipment to market, admissions to a profession, limitations of production or sales and notifications of economic activity. The results of the study performed with proprietary methodology indicate an increase of economic areas subject to restrictions in the period under review (from 108 areas in 1989 up to 175 areas in 2003) and an increased number of restrictions (from 403 cases in these areas in 1989 up to 607 cases in 2003). Excessive restrictions in economic activity implemented by the state result in weakened competitiveness of the economy and may cause a long-term high unemployment rate and decreased economic growth. The presented method should be applied to constant monitoring of legislative activities, both quantitative and qualitative. Moreover, it may help calculate administrative costs to be borne by entrepreneurs and it may be used in further international comparative studies.